A review of CO2 catalytic regeneration research based on MEA solution - Yang, Zhiyuan; Shen, Yuhang; Yang, Haoran; Yi, Hui; Guo, Hao; Zhang, Xiaoliang (Frontiers in Energy Research, 2023)
In recent years, the rapid increase of CO2 emission has caused severe environmental issues. The environmental concern has made how to reduce the carbon emissions become a hot topic. Many scholars and research teams believe that the organic amine chemical absorption technology is the most favored and promising carbon capture technology due to its highly CO2 removal effectiveness. However, it is not applied wildly in industrial environment since the desorption process energy consumption is too much, over 4 GJ/t CO2. Many researchers report that catalysts can help to reduce the desorption energy. And it is generally assumed that four key properties of solid acid catalysts determined the performance of solid acid catalysts in the process of CO2 desorption: the total number of acid sites; specific surface area; the ratio of Brønsted acid sites to Lewis acid sites; the amount of Brønsted acid sites. Therefore, this paper reviews the recent research on the effect of different catalysts on the energy consumption of CO2 desorption and the progress of research on improving catalyst performance. Also, it provides views on the possible problems in practical industrial applications.